Inconclusive Cystic Fibrosis neonatal screening results: long-term psychosocial effects on parents - Perobelli, Sandra; Zanolla, Luisa; Tamanini, Anna; Rizzotti, Paolo; Maurice Assael, Baroukh; Castellani, Carlo (Acta Paediatrica, 2009)
Aim:  Cystic Fibrosis (CF) Newborn Screening occasionally identifies neonates where a CF diagnosis can neither be confirmed nor excluded. To assess how parents of these infants cope with this ambiguous situation. Methods:  Parents of 11 children with Ambiguous Diagnosis (group AD) were compared with parents of 11 children diagnosed with CF through neonatal screening [group Cystic Fibrosis Diagnosis (CFD)] and with parents of 11 Healthy Control children (group HC) matched for gender and age. Results:  The emotional reaction to the inconclusive result was less pronounced in AD than in CFD (p = 0.003), and AD parents considered their infants as healthy as controls. Parents’ anxiety about their child’s health is stronger in CFD than in AD (p < 0.05) and HC (p < 0.001). Long‐term emotional distress was rated similarly in AD and CFD, and greater than in HC (p = 0.0003). The parent/child relationship was less influenced in AD than in the CF group (p = 0.03). Seven AD and CFD parents changed their family planning projects. Conclusion:  Inconclusive neonatal screening results appear to be understood and associated with lower anxiety levels than CF diagnosis. Concern about the child’s health is similar to healthy controls and lower than in parents of CF children.